PENGUNGKAPAN KEBERADAAN TOKOH SEMAR DALAM PROFESI AKUNTAN - Lila Alwyah; Audrie Clarissa Bepe (E-Jurnal Akuntansi TSM, 2026)
This research aims to identify the characteristics of Semar's character which are reflected in the character of accountants, with a focus on the application of his professional code of ethics The method used in this research is qualitative using an interpretive paradigm. Data was obtained through interviews with auditors and accounting service office owners. This research found that the characteristics of Semar are reflected in accountants such as Manunggaling budhi, lathi and experti, devotion, role model, sense of awareness and Manunggaling kawula Gusti. This characteristic is inherent in accountants in carrying out their profession. So an accountant is not only called a "scorer", but also has integrity, a sense of intelligence and other things which are reflected in the character Semar. This research connects aspects of Semar's character with the accounting profession, opening new views on the role of accountants in society. This research contributes to increasing understanding of ethics and integrity in the accounting profession, as well as strengthening public trust in this profession.